Detecting the Nation: Fictions of Detection and the Imperial Venture - Reitz, Caroline
In Detecting the Nation, Reitz argues that detective fiction was essential both to public acceptance of the newly organized police force in early Victorian Britain and to acclimating the population to the larger venture of the British Empire. In doing so, Reitz challenges literary-historical assumptions that detective fiction is a minor domestic genre that reinforces a distinction between metropolitan center and imperial periphery. Rather, Reitz argues, nineteenth-century detective fiction helped transform the concept of an island kingdom to that of a sprawling empire; detective fiction placed imperialism at the center of English identity by recasting what had been the suspiciously un-English figure of the turn-of-the-century detective as the very embodiment of both English principles and imperial authority. She supports this claim through reading such masters of the genre as Godwin, Dickens, Collins, and Doyle in relation to narratives of crime and empire such as James Mill's History of British India, narratives about Thuggee, and selected writings of Kipling and Buchan. Detective fiction and writings more specifically related to the imperial project, such as political tracts and adventure stories, were inextricably interrelated during this time.